Relationship between the white blood cell count and some lipid profile parameters in cancer patients with myocardial infarction - E. G. Skorodumova; E. A. Skorodumova; V. A. Kostenko; A. V. Siverina (Российский кардиологический журнал)
Hokkaido University (Tsumita T, 2022) researchers found that endothelial cells accumulate low-density lipoproteins (LDL) in tumor blood vessels. At the same time, the endothelium carries out neutrophil chemotaxis, which perform an immunosuppressive function contributing to cancer progression.Aim. To search for the relationship between the white blood cell (WBC) count and some lipid profile parameters in cancer patients with myocardial infarction (MI).Material and methods. We examined 319 patients who were treated at Dzhanelidze Research Institute of Emergency Medicine in 2018-2023, which were divided into three groups: MI in combination with an active cancer — 132 patients (Group I), MI+cancer in history — 58 patients (Group II), MI without cancer — 129 patients (Group III). Following laboratory data used in routine practice were assessed: WBC count, relative neutrophil count, total cholesterol, low-density lipoproteins.Results. Cancer patients with MI are characterized by higher WBC and neutrophil count than in other samples However, the total cholesterol level was significantly lower in this sample, and the LDL level was not significantly different. Patients with MI and previous cancer occupied an intermediate position between groups I and III in terms of studied parameters.Conclusion. In general, data on the role of cholesterol levels in cancer patients are contradictory. In particular, some studies have shown that elevated cholesterol levels are a potential risk factor for cancer. In our study, as in a number of others, no significant associations were identified between elevated cholesterol levels and the presence of cancer. Our study is a step towards understanding the connection between the cholesterol concentration and the immune response in cancer patients with MI.